How Do We Combat Bogus Medicines in the Age of the COVID-19 Pandemic? - Tesfaye, Wubshet (Am J Trop Med Hyg, 2020)
The COVID-19 pandemic has brought concurrent challenges. The increased incidence of fake and falsified product distribution is one of these problems with tremendous impact, especially in low- and middle-income countries. Up to a tenth of medicines including antibiotics and antimalarial drugs in the African market are considered falsified. Pandemics make this worse by creating an ecosystem of confusion, distraction, and vulnerability stemming from the pandemic as health systems become more stressed and the workload of individuals increased. These environments create opportunities for substandard and falsified medicines to be more easily introduced into the marketplace by unscrupulous operators. In this work we discuss some of the challenges with fake or falsified product distribution in the context of COVID-19 and proposed strategies to best manage this problem.